2018
DOI: 10.1590/s0100-204x2018000500013
|View full text |Cite
|
Sign up to set email alerts
|

Functional response of Trichogramma pretiosum on Trichoplusia ni eggs at different temperatures and egg densities

Abstract: The objective of this work was to determine the functional response of the parasitoid Trichogramma pretiosum on Trichoplusia ni eggs at different temperatures (20, 25, and 30ºC) and egg densities (5, 10, 15, 20, 25, and 30 eggs). The logistic regression showed a type-II functional response for all temperatures. The search efficiency of T. pretiosum was reported as 0.049±0.0019, 0.069±0.0042 and 0.068±0.0033 per hour, and the estimated handling times were 1.82±0.0424, 1.69±0.0398, and 1.54±0.0498 hour at 20, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 9 publications
1
2
0
7
Order By: Relevance
“…Also in the study by Oliveira et al (2017) there was also a reduction in the values of parasitism, emergence, adult egg period and sexual ratio, when the temperature ranged from 25 °C to 33 °C. Similar tendency were also observed in other studies, regardless of the host (Carvalho et al, 2017;Milanez, Carvalho, Lima, & Pratissoli, 2018). However, despite the temperature stress condition of T. pretiosum females in this study, it was observed that the longevity, tibial length, number of parasitized eggs and adult emergence rate increased.…”
Section: Resultssupporting
confidence: 91%
“…Also in the study by Oliveira et al (2017) there was also a reduction in the values of parasitism, emergence, adult egg period and sexual ratio, when the temperature ranged from 25 °C to 33 °C. Similar tendency were also observed in other studies, regardless of the host (Carvalho et al, 2017;Milanez, Carvalho, Lima, & Pratissoli, 2018). However, despite the temperature stress condition of T. pretiosum females in this study, it was observed that the longevity, tibial length, number of parasitized eggs and adult emergence rate increased.…”
Section: Resultssupporting
confidence: 91%
“…This behavior is also mentioned by Price (1975) as Holling type II functional response, as parasitism increases at a decreasing rate with the increase in the number of hosts, a behavior that is commonly observed in parasitoids and insect predators (Holling 1961). Milanez et al (2018) also recorded the same type of functional response, with the same parasitoid, in eggs of Trichoplusia ni (Hübner) (Lepidoptera: Noctuidae), concluding that the decrease in oviposition due to the limitation of parasitoid eggs is due to its endocrine oviposition control system, even if eggs are available, not due to the absence of oogenesis, but due to the regulation of neurohormones (Reznik et al 2003).…”
Section: Discussionmentioning
confidence: 58%
“…O tempo máximo de sobrevivência foi 15 dias (Figura 2). Verifica-se que a temperatura pode não ser o único fator isolado responsável pelas variações na longevidade das fêmeas, pois outros fatores como fotoperíodo, umidade relativa, competição inter e intraespecífica e presença do hospedeiro podem interferir nas características biológicas de um parasitoide (PEREIRA PAES et al, 2018;MILANEZ et al, 2018;PRATISSOLI et al, 2019).…”
Section: Resultsunclassified
“…A longevidade de fêmea e a capacidade de parasitismo, variam de acordo com a temperatura e o hospedeiro. Portanto, é crucial o conhecimento da influência da temperatura e do hospedeiro no ciclo de vida e nos parâmetros biológicos do parasitoide (MILANEZ et al, 2018;PRATISSOLI et al, 2019).…”
Section: Introductionunclassified